Alzheimer’s disease as a causal risk factor for diabetic retinopathy: a Mendelian randomization study - Ouyang, Fu; Yuan, Ping; Ju, Yaxin; Chen, Wei; Peng, Zijun; Xu, Hongbei (Frontiers in Endocrinology, 2024)
These results were corroborated by DR GWAS datasets from IEU OpenGWAS. The MR-Steiger test confirmed a significant association of all identified instrumental variables (IVs) with AD. While a potential causal effect of DR and its subtypes on AD was identified, the robustness of these results was constrained by a low power value. FUMA analysis identified OARD1, NFYA, TREM1 as shared risk genes between DR and AD, suggesting a potential genetic overlap between these complex diseases.Discussion: This study underscores the contribution of AD to an increased risk of DR, as well as NPDR and PDR subtypes, underscoring the necessity of a holistic approach in the management of patients affected by these conditions.